2002
DOI: 10.1007/s00248-002-2012-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Dynamics across a Floristic Gradient in a Temperate Upland Grassland Ecosystem

Abstract: Alterations in soil bacterial communities across a transect between a semi natural upland grassland and an agriculturally improved enclosure were assessed using culture-based methods and a nucleic-acid-based method, terminal restriction fragment length polymorphism (TRFLP). While plant diversity decreased across the transect towards the improved area, numbers of 16S rDNA terminal restriction fragments increased, indicating an increase in numbers of bacterial ribotypes. Bacterial numbers, microbial activity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 47 publications
9
96
1
2
Order By: Relevance
“…It is possible, as suggested by Wardle [59] that plant diversity exerts a detectable effect on soil microbial communities only when plant diversity increases plant productivity. This finding is supported by Zak et al [61], where plant diversity was associated with increases in productivity, as well as Brodie et al [8], where microbial diversity was positively related to soil organic matter concentrations. We did not have productivity estimates for the secondary succession sites in our study, but we observed an increase in soil carbon concentrations with plant diversity, which may be a reasonable index of plant productivity [39]; thus, our study also supports the Wardle [59] hypothesis.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…It is possible, as suggested by Wardle [59] that plant diversity exerts a detectable effect on soil microbial communities only when plant diversity increases plant productivity. This finding is supported by Zak et al [61], where plant diversity was associated with increases in productivity, as well as Brodie et al [8], where microbial diversity was positively related to soil organic matter concentrations. We did not have productivity estimates for the secondary succession sites in our study, but we observed an increase in soil carbon concentrations with plant diversity, which may be a reasonable index of plant productivity [39]; thus, our study also supports the Wardle [59] hypothesis.…”
Section: Discussionsupporting
confidence: 60%
“…In fact, soil C/N, an indicator of the relative quality of soil organic matter [41], was the abiotic variable most related to differences in microbial community composition across the plant diversity gradient and among monocultures. We expected soil carbon concentrations to play an important role as well, given the importance of available energy in structuring communities [8,38], but we found no evidence of such a link. Although we did find a correlation between microbial community differences and soil C/N, it was always low (the correlation coefficient never exceeded 0.10).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This resulted in a lower TRF number than is 266 reported in some other studies (Kennedy et al 2005; Brodie et al 2008). However, reducing 267 the number of TRFs to focus on the dominant types helps to eliminate artefactual results 268 (Singh et al 2006), and allowed us to use multivariate statistics.…”
Section: Introduction 56 57mentioning
confidence: 72%